*This preview shows
page 1. Sign up
to
view the full content.*

**Unformatted text preview: **) y = 0. b) Without explicitly solving the equation x 2 y + (sin x ) y + (cos x ) y = 0, describe its solutions. 4. Consider the equation y + e-x y = 0. a) Let f ( x ) be a solution of y + e-x y = 0. Show that y ( x ) = (-x ) is a solution of y + e x y = 0. b) Without explicitly solving the equation y + e-x y = 0, describe the behavior of its solutions in as much detail as you can....

View
Full
Document